2001
DOI: 10.1046/j.1440-1681.2001.03482.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects Of L‐Arginine And Furosemide On Blood Pressure And Renal Function In Volume‐Expanded Rats

Abstract: 1. The aim of the present study was to investigate the effects of L-arginine (L-Arg) on blood pressure and water and electrolyte excretion in control and extracellular fluid volume-expanded rats (10% bodyweight with 0.9% NaCl) and to determine whether diuretic treatment with furosemide (FUR) can be optimized by the administration of L-Arg in this model. 2. Both groups of animals were anaesthetized, divided into groups and treated with either 7.5 mg/kg FUR, 250 mg/kg L-Arg, 1 mg/kg NG-nitro-L-arginine methyl es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Given there are alternative options available for hypertension management, it may be prudent to avoid this class of antihypertensive for chronic administration with a VEGF signaling inhibitor. Use of some loop diuretics such as furosemide, which blocks renal chloride and sodium reabsorption, should also be avoided as their efficacy is impaired by inhibitors of NO (39). Inhibition of VEGF signaling decreases NO activation acutely, as well as the synthesis of NO synthase chronically (40), which would significantly reduce the effectiveness of furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…Given there are alternative options available for hypertension management, it may be prudent to avoid this class of antihypertensive for chronic administration with a VEGF signaling inhibitor. Use of some loop diuretics such as furosemide, which blocks renal chloride and sodium reabsorption, should also be avoided as their efficacy is impaired by inhibitors of NO (39). Inhibition of VEGF signaling decreases NO activation acutely, as well as the synthesis of NO synthase chronically (40), which would significantly reduce the effectiveness of furosemide.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Tucker and Blantz (159) reported a decrease in mean arterial pressure in animals treated with furosemide, but without volume repletion (159); this was accompanied by a decrease in single nephron glomerular filtration rate (SNGFR), surprisingly mediated by a decrease in glomerular permeability coefficient LpA, but not by a decrease in net ultrafiltration pressure. Surprisingly, Costa et al reported similar decreases in MAP after furosemide administration in rats in normovolemic vs. volume-expanded animals (33). To complicate this further, furosemide could elicit a natriuresis in an individual with decompensated heart failure, leading to a more favorable end-diastolic pressure and increased cardiac output (98).…”
Section: Questions Pertaining To the Natriuretic Response To Furosemidementioning
confidence: 96%
“…In addition, it was reported that the activation of renal NO pathway induced a diuretic and natriuretic response. Alterations in intrarenal NO production may be involved in the pathogenesis of chronic renal failure [26]. …”
Section: Discussionmentioning
confidence: 99%